Cover Image. Issue 4 (11th February 2019) - Aono, Yuri; Watanabe, Yuriko; Ishikawa, Manabu; Kuboyama, Noboru; Waddington, John L.; Saigusa, Tadashi
Abstract : The cover image is based on the In vivo neurochemical evidence that stimulation of accumbal GABAA and GABAB receptors each reduce acetylcholine efflux without affecting dopamine efflux in the nucleus accumbens of freely moving rats by Yuri Aono et al., DOI:10.1002/syn.22081 .